Morphometric investigations to assess the compatibility of mandible and skull. (May 2018) - Preissler, Sandra; Verhoff, Marcel A.; Ramsthaler, Frank; Holz, Franziska; Gehl, Axel; Koelzer, Sarah C.
Highlights: To find out whether a mandible meshes with a skull, two new indices were developed. Sex-specific 2.5–97.5 percentile ranges of the indices were determined. The indices are applicable to exclude a match, rather than to prove one. Abstract: When a morphologically separated skull and mandible are found in the same case context, the possibility of a match arises. Two criteria with which to determine a match are the rough articulation between the mandibular condyles and cranial base itself and, most importantly, the fit of the teeth. However, when there has been intravital or postmortem tooth loss, this important criterion is not available. To date, only Reichs (1989) has investigated further compatibility criteria to solve the question of putative commingling in a case where a mandible seemed to originate from a female, while all other bones originated from a male individual. In a different reported case (Preißler et al. 2017), a mandible seemed too big for a skull; DNA analysis, however, confirmed that both originated from the same female individual. To investigate the metric relationship between mandible and skull we measured the postmortem CT data records of 223 corpses (virtual skulls) in OsiriX © MD for the following linear parameters: bicondylar breadth (KDB), biradicular breadth (AUB), and bizygomatic breadth (ZYB). The indices KDB/ZYB and KDB/AUB were developed and used to define ranges for matches and mismatches. Furthermore, the intra-observer reliability for the method was assessed. An intraclass correlation coefficient of >0.99 for every parameter showed that the used measurements are highly reliable. The 2.5–97.5 percentile for the KDB/AUB index lay between 0.91 and 1.05, while the range for the KDB/ZYB index was between 0.87 and 1.00. Within these ranges, it is possible to roughly assess whether or not a mandible and skull might be compatible, even if this can only be verified by forensic DNA analysis. If an index value lies outside these ranges, it can be assumed that skull and mandible do not match. Future studies should include more samples from a broader population spectrum so that these metric relationships can be used for different populations.